A SURVEY REGARDING MANGO FRUIT BORER INFESTATION IN MANGO ORCHARDS OF PUNJAB PAKISTAN - LARAIB, T; HAMEED , A; KHAN , AH; KHAN , AA; IQBAL , A; IMRAN , M; MUSTAFA , G; MUHAMMAD , N; ALI, F; HUSSAIN , R; et al. (Biological and Clinical Sciences Research Journal, 2024)
Mango is an important tropical fruit crop grown in most parts of the world including India, Pakistan, China, Bangladesh, Burma, Thailand, Japan, New Zealand, Australia, Indonesia, Africa, Brazil, Mexico and some US states. Mangan o is an important fruit crop for Pakistan due to its delicious taste, rich in vitamins A and C-and high-income returns to mango growers. However, in recent years a new pest problem mango fruit borer extensively damaged mango fruit crop in all mango growing districts of Punjab and Sindh. This insect was previously not even recognized as an important pest of mangoes in Pakistan among farmers and the scientific community, however since 2017, very serious complaints have been received from mango orchard owners regarding damage caused by MFB in the fruit clusters. Hence a survey was conducted in four districts of Punjab Pakistan viz., Multan, Muzaffargarh, Khanewal, and Rahim Yar Khan. About 145 mango growers were randomly chosen for interviews to learn about farmer perceptions and management of mango fruit borer. A series of open-ended and closed-ended questions were asked. Data was analyzed through the Chi-square test using Statistix 8.1 software. Farmers were asked various questions regarding farmers' identification of MFB stages and the nature of the damage, varietal preference of MFB, resting or hibernating places of the pest, insecticides used to control the pest, weeds as the reservoir of the pest and many more. Overall, most of the farmers were primarily qualified, males and had orchard sizes of 2 to 10 acres. Farmers reported that Sindhri was mostly affected by variety. Farmers used insecticides to control the pest menace and achieved around 40-80 % control. The knowledge about species recognition was very low among farmers. Based on this survey, we recommend farmer training programs regarding pest management, enhancing awareness among farmers regarding pest attacks, pest scouting, pest recognition and incorporation of cultural control techniques along with insecticides as a necessary part of pest management should be explained.